Simplified drone game for initial remedial intervention for dyspraxia among kids / Mohd Sahrin Ab Satar and Azlan Abdul Aziz - Ab Satar, Mohd Sahrin; Abdul Aziz, Azlan (College of Computing, Informatics, and Mathematics, 2024)
Dyspraxia, alternatively referred to as developmental coordination disorder (DCD), is an early-onset neurodevelopmental disorder. It interferes with coordination and motor (movement) abilities. A diverse array of difficulties pertaining to movement and coordination can be impacted by dyspraxia, thereby presenting obstacles to tasks such as writing, operating a bicycle, or fastening buttons. The research indicates that children diagnosed with dyspraxia consistently struggle with coordination issues, movement difficulties, and cognitive impairments. This research aims to create a simplified drone game that can be utilised by children with dyspraxia as an initial remedial intervention. Rapid Application Development (RAD) was utilised for this project because it offered a more secure and expedient development process, which was ideal for this project. This game application utilises the International Classification of Functioning, Disability, and Health (ICY-CY) framework, and the observation method is being employed to assess the game's efficacy. The result indicates that adjustments should be made to the activities in order to increase their efficacy in aiding children with dyspraxia during the remedial process. Further development could be made by incorporating a wider range of challenges and quizzes. At the end of this project a total of 72.73% of players managed to finish the game faster than at previous games and as many as 93% of research results show the effectiveness of this game in helping remedial intervention for dyspraxia among kids.